Growth and Accumulation of Secondary Metabolites in Perilla as Affected by Photosynthetic Photon Flux Density and Electrical Conductivity of the Nutrient Solution - Lu, Na; Bernardo, Emmanuel L.; Tippayadarapanich, Chayanit; Takagaki, Michiko; Kagawa, Natsuko; Yamori, Wataru (Frontiers in Plant Science, 2017)
The global demand for medicinal plants is increasing. The quality of plants grown outdoors, however, is difficult to control. Myriad environmental factors influence plant growth and directly impact biosynthetic pathways, thus affecting the secondary metabolism of bioactive compounds. Plant factories use artificial lighting to increase the quality of medicinal plants and stabilize production. Photosynthetic photon flux density (PPFD) and electrical conductivity (EC) of nutrient solutions are two important factors that substantially influence perilla (Perilla frutescens, Labiatae) plant growth and quality. To identify suitable levels of PPFD and EC for perilla plants grown in a plant factory, the growth, photosynthesis, and accumulation of secondary metabolites in red and green perilla plants were measured at PPFD values of 100, 200, and 300 µmol m−2 s−1 in nutrient solutions with EC values of 1.0, 2.0, and 3.0 dS m−1. The results showed significant interactive effects between PPFD and EC for both the fresh and dry weights of green perilla, but not for red perilla. The fresh and dry weights of shoots and leafy areas were affected more by EC than by PPFD in green perilla, whereas they were affected more by PPFD than by EC in red perilla. Leaf net photosynthetic rates were increased as PPFD increased in both perilla varieties, regardless of EC. The perillaldehyde concentration (mg g−1) in red perilla was unaffected by the treatments, but accumulation in plants (mg per plant) was significantly enhanced as the weight of dry leaves increased. Perillaldehyde concentrations in green perilla showed significant differences between combinations of the highest PPFD + the highest EC and the lowest PPFD + the lowest EC. Rosmarinic acid concentration (mg g−1) was increased in a combination of low EC and high PPFD conditions. These results suggest that applying a PPFD of 300 µmol m−2 s−1 with an EC of 2.0 or 3.0 dS m−1 for red perilla, and a PPFD of 200 or 300 µmol m−2 s−1 with an EC of 3.0 dS m−1 for green perilla are suitable to obtain a sufficient quantity of good quality perilla plants in a plant factory.